NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Comparison of chemical compositions in air particulate matter during summer and winter in Beijing, China - Rui Chen; Jing Cheng; Jungang Lv; Lijun Wu; Jing Wu (Environmental Geochemistry and Health, 2017)

Occurrence and profiles of polybrominated diphenyl ethers (PBDEs) in riverine sediments of Shanghai: a combinative study with human serum from the locals - Ming-Hong Wu; Ben-Tuo Xu; Gang Xu; Ming-Nan Wang; Jing Ma; Chen-Yuan Pan; Rui Sun; Tao Han; Liang Tang (Environmental Geochemistry and Health, 2017)

Apigenin attenuates streptozotocin-induced pancreatic β cell damage by its protective effects on cellular antioxidant defense - Ning Wang; Wen Jing Yi; Lu Tan; Jia Hui Zhang; Jiamin Xu; Yi Chen; Mengting Qin; Shuang Yu; Jing Guan; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Microbial profiles of a drinking water resource based on different 16S rRNA V regions during a heavy cyanobacterial bloom in Lake Taihu, China - Junyi Zhang; Congming Zhu; Rui Guan; Zhipeng Xiong; Wen Zhang; Junzhe Shi; Yi Sheng; Bingchuan Zhu; Jing Tu; Qinyu Ge; Ting Chen; Zuhong Lu (Environmental Science and Pollution Research, 2017)

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

Biological traits yield divergent phylogeographical patterns between two aphids living on the same host plants - Fang Fang; Jing Chen; Li‐Yun Jiang; Rui Chen; Ge‐Xia Qiao (Journal of Biogeography, 2017)
Aim Animals' phylogeographical patterns are frequently explained by Pleistocene glacial fluctuations and topographical environments. However, species‐specific biological traits are thought to have profound impacts on distribution patterns, particularly in aphids. We hypothesize that the phylogeographical patterns and/or population dynamics of two sympatric aphids may be different due to their different reproductive modes and feeding sites, even though they share the same hosts and environmental conditions. Location China. Methods We explored our hypothesis in Chaitophorus saliniger and Tuberolachnus salignus , two aphids that share the same host plants (genus Salix ) but differ biologically. Chaitophorus saliniger is characterized by alternating sexual and asexual reproduction and only feeds on willow leaves, whereas T. salignus has obligate asexual reproduction and feeds on trunks and branches. The genetic diversity, population structure and demographic history of the aphids were analysed based on both mitochondrial DNA (cytochrome c oxidase subunit I and cytochrome b ) and nuclear DNA (translation elongation factor 1 alpha). Ecological niche models ( ENM s) were used to explore historical changes in distribution. The chief environmental variables that discriminate the different haplogroups were identified through multivariate statistical analysis. Results There were striking differences in the phylogeographical patterns between the species. The sexual C. saliniger exhibited higher genetic diversity and population variations than the asexual T. salignus . According to genetic analyses and ENM s, both species experienced glacial contraction and post‐glacial expansion. Multivariate statistical analysis revealed that the climatic differences between the divergent haplogroups were explained by principal components mainly loaded with temperature and elevation. Main conclusions Our results suggest that species‐specific biological traits and historical climate fluctuations have both shaped the current phylogeographical patterns of both aphid species. Their distinct genetic diversity and population structures highlight the importance of intrinsic biological features in driving phylogeographical patterns.

Efficient Generation of Functionally Active Spinal Cord Neurons from Spermatogonial Stem Cells - Hao Yang; Cuicui Liu; Bo Chen; Jing An; Rui Zhang; Qian Zhang; Jingjing Zhao; Baorong He; Ding-Jun Hao (Molecular Neurobiology, 2017)

Application of Biotic Ligand Model in Predicting Copper Acute Toxicity to Carp (Cyprinidae) - Wanbin Wang; Qibin Liang; Jing Zhao; Rui Chen (Bulletin of Environmental Contamination and Toxicology, 2017)